2017
DOI: 10.1139/facets-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Enemy escape: A general phenomenon in a fragmented literature?

Abstract: Many populations are thought to be regulated, in part, by their natural enemies. If so, disruption of this regulation should allow rapid population growth. Such “enemy escape” may occur in a variety of circumstances, including invasion, natural range expansion, range edges, suppression of enemy populations, host shifting, phenological changes, and defensive innovation. Periods of relaxed enemy pressure also occur in, and may drive, population oscillations and outbreaks. We draw attention to similarities among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 147 publications
(194 reference statements)
0
22
0
Order By: Relevance
“…For example, the monophagous gall-forming flies, Lipara (Diptera: Chloropidae) were introduced along with invasive P. australis from Europe into North America and it was found that in some areas of the adventive range the invasive P. australis genotypes had higher attack rates from Lipara than in the ancestral range (Allen et al ., 2015). Lastly, it may be important to consider that for A. donax release from herbivory may not be the leading factor for its invasive success; some plants are instead largely controlled by ecological factors (Keane & Crawley, 2002; Colautti et al ., 2004; Prior et al ., 2015; Mlynarek et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the monophagous gall-forming flies, Lipara (Diptera: Chloropidae) were introduced along with invasive P. australis from Europe into North America and it was found that in some areas of the adventive range the invasive P. australis genotypes had higher attack rates from Lipara than in the ancestral range (Allen et al ., 2015). Lastly, it may be important to consider that for A. donax release from herbivory may not be the leading factor for its invasive success; some plants are instead largely controlled by ecological factors (Keane & Crawley, 2002; Colautti et al ., 2004; Prior et al ., 2015; Mlynarek et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gall inducers suffer from extremely high rates of parasitoid mortality, and traits that improve their ability to resist parasitoid attack, even temporarily, should still be strongly selected for, given that even temporary or incomplete enemy escape can lead to diversification (Stone and Schönrogge , Mlynarek et al. ). Even in communities that are not top‐down regulated, mortality‐inducing agents can still act as selective mechanisms.…”
Section: Nectar‐secreting Galls and The Evolution Of Ant‐mutualismsmentioning
confidence: 99%
“…Rapid phenology is commonly observed in arid systems, and this has long been presumed to be due to selection to escape the late season drought and unpredictable hydric environments of arid areas (Aronson et al 1992;Thuiller et al 2004;Levin 2006;Volis 2007). "Phenological escape" from insect herbivory has been shown for multiple plant taxa (Pilson 2000;Krimmel & Pearse 2016;Mlynarek et al 2017), but mammalian herbivore control on plant phenology and distributions in arid environments remains relatively unexplored.…”
Section: Generality Of a Generalist Predator Enforcing Range Limitsmentioning
confidence: 99%